The intergenerational effects of economic sanctions - Safoura Moeeni (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2021)
While economic sanctions are successful in achieving political goals, can hurt the civilian population. These negative effects could be even more detrimental and long-lasting for future generations. I estimate the effects of economic sanctions on children's education by exploiting the United Nations sanctions imposed on Iran in 2006. Using the variation in the strength of sanctions across industries and difference-in-differences with synthetic control analyses, I find that the sanctions decreased children's total years of schooling by 0.1 years and the probability of attending college by 4.8 percentage points. Moreover, households reduced education spending by 58% - particularly on school tuition. These effects are larger for children who were exposed longer to the sanctions. The results imply that sanctions have a larger effect on the income of children than their parents. Therefore, ignoring the effects of sanctions on future generations significantly understates their total economic costs.
Keywords: I20; E24; F51; 330; Education; Parental investment; Economic sanctions; Intergenerational effects